(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
This study investigates the possibility of using rice husk ash as an additive to develop an environmentally friendly and low-cost drilling fluid system. The rice husk ash was added as an additive to water-based bentonite drilling fluids at different concentrations ranging from 2 wt% to 15 wt%. Rheological and filtration properties of each drilling fluid developed were measured by using a viscometer and standard low-pressure low-temperature filter press. Subsequently, cutting carrying index, minimum annulus velocity required to clean bottom of the well efficiently, flow behaviour index and permeability of mud cakes of the formulated systems were calculated in order to assess performance of the systems. The results demonstrated that the rheological and properties were improved depending on concentration of rice husk ash introduced. With the introduction of 15 wt% concentration of rice husk ash, while apparent viscosity and yield point increased by 60% and 183%, respectively, thixotropy and plastic viscosity decreased by 29% and 63%, respectively. On the other hand, drilling fluid with 4% wt% content of rice husk ash reduced the fluid loss by 10%. Moreover, results showed that cutting carrying index, minimum annulus velocity required to clean bottom of the well efficiently and flow behaviour index of the enhanced with the exploitation of rice husk ash in the drilling fluid. This study showed that rice husk ash as a promising additive to use in the water-based bentonite drilling fluids when properly implemented, and hence reducing the impact on the environment, and the total cost for drilling.